THE EFFECT OF USING MIND MAPPING TECHNIQUE ON WRITING DESCRIPTIVE TEXT AT THE TENTH GRADE STUDENT’S OF SMA TAMAN SISWA BINJAI - Meycin Sri Rahmadani; Conny conny; Ahmad Azrai Aziz (STKIP Budidaya Binjai, 2021)
The objective of this resarch was to find out the effect of using mind mapping technique on students’ writing descriptive text. This study applied quasi-experimental research. This study was conducted of the tenth grade students’ of SMA Swasta Taman Siswa Binjai as the population study. The sample was taken by using cluster random sampling, with 70 students as the sample. As the experimental class, the writer used class X-IPS 1 which consisted of 35 students and for the controlled class, the writer used class X-IPA 2 that consist of 35 students. The data collected from this study were analyzed by using t-test formula. The result from calculating the data was found that the value of t-observed ( ) was higher than the value of t-table ( ). The result of was 4,05 since the in degree of significant 5% was 1,66. It shows that the comparison of and was 4,05 1,66. Therefore the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. In other words, there was an effect of using mind mapping technique on writing descriptive text at the tenth grade students’ of SMA Swasta Taman Siswa Binjai.